Pemodelan Spasial Kesesuaian Habitat Rekrekan (Presbytis comata fredericae Sody, 1930) menggunakan Analisis MaxEnt di Hutan Petungkriyono, KPH Pekalongan Timur - Artaka, Arrayaana; Rahardjo, Poegoeh Prasetyo; Kurniawan, Iwan (JURNAL GREEN HOUSE, 2026)
Petungkriyono Forest is a conservation area as a habitat for endemic animals on the island of Java, such as Rekurkan (Presbytis comata fredericae Sody, 1930). One form of spatial fairness of living space is through the Natural Specialty Displaying (ENM) approach. This exploration aims to determine the feasibility of the Rekkerjaan environment in the Petungkriyono Forest, KPH East Pekalongan. The research was conducted from April to May 2023. The habitat suitability model uses data on encounter coordinates and environmental variables of the Rekkerjaan habitat. The data is then analyzed using the Maximum Entropy (MaxEnt) algorithm, a model of Rekrekan habitat suitability can be built. The research results showed three models of habitat suitability categories, high 1,554 ha (26%), medium 1,562 ha (27%), and low 2,658 ha (46%). The evaluation of the Rekrekan habitat suitability model in the Petungkriyono Forest has a very good AUC value and model accuracy of 0.916